STRATEGI PENGEMBANGAN TERNAK AYAM RAS PETELUR DI KECAMATAN GADINGREJO KABUPATEN PRINGSEWU - Suf Ajizah; Sudarma Widjaya; Suriaty Situmorang (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2018)
The research aims to determine the position strategy and the priority strategy of layer chicken farming development strategy.  The research is a case study of layer chicken farming in Gadingrejo Subdistrict of Pringsewu District which has been chosen purposively.  Data were collected in Desember 2016.  Respondents were three farmers consist of large scale, medium scale, and small scale farmers.  The analytical tool SWOT analysis was used in this study.  The results showed that large scale, medium scale, and small scale of layer chicken farming businesses were in quadrant I with the position of aggressive growth strategy.  The development priority strategy of large scale is to increase relationships with suppliers so that the development of chicken livestock centers can be achieved.  The development priority strategy of medium scale is to improve customers so that farmers are able to compete. The development priority strategy of small scale is to maintain a strategic location for easy reaching and meet the demand of eggs by costumers.Key words: development strategy, layer chickens, SWOT analysis